2020
DOI: 10.1002/oby.23043
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Trends and Associations with Types of Physical Activity and Sedentary Behavior in US Adults: National Health and Nutrition Examination Survey, 2007‐2016

Abstract: Objective Physical activity (PA) and sedentary behavior (SB) have been linked to adult adiposity. This research aims to explore 10‐year (2007‐2016) trends in obesity and abdominal obesity prevalence and associations with different types of PA and SB among US adults. Methods National Health and Nutrition Examination Survey (NHANES) data were used with 20‐ to 64‐year‐old adults (n = 20,360; mean age: 41.9 years; male: 50.5%; non‐Hispanic White: 64.3%). Sex‐ and sex‐ and race‐specific linear trends in the prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…88 cm) is also highest in non-Hispanic Black (74%) and Hispanic (75%) women, with a marked increasing trend in prevalence among Hispanic women. 18 Complex interrelated factors explain the obesity epidemic, including policy, environmental factors (e.g., food supply and marketing, built environment), behavioral patterns (poor diets, sedentary lifestyles), and genetic predisposition, 17 and these vary across populations. Such racial/ethnic disparities in obesity burden were also observed among women with a history of cancer, with breast cancer survivors specifically having a faster increase in obesity prevalence compared with adults without a history of cancer.…”
Section: Racial/ethnic Disparities In Obesity and Breast Cancer Risk And Survivalmentioning
confidence: 99%
“…88 cm) is also highest in non-Hispanic Black (74%) and Hispanic (75%) women, with a marked increasing trend in prevalence among Hispanic women. 18 Complex interrelated factors explain the obesity epidemic, including policy, environmental factors (e.g., food supply and marketing, built environment), behavioral patterns (poor diets, sedentary lifestyles), and genetic predisposition, 17 and these vary across populations. Such racial/ethnic disparities in obesity burden were also observed among women with a history of cancer, with breast cancer survivors specifically having a faster increase in obesity prevalence compared with adults without a history of cancer.…”
Section: Racial/ethnic Disparities In Obesity and Breast Cancer Risk And Survivalmentioning
confidence: 99%
“…There have been drastic changes in lifestyle behaviors over the past few decades, including reductions in physical activity (PA) and higher consumption of calorie-dense food and beverages (Agustina et al, 2021;Zhang et al, 2021). These unhealthy lifestyles are linked to increasing rates of obesity and type 2 diabetes mellitus in adults and youth (Lawrence et al, 2021;Ogden et al, 2020;Wang et al, 2021) and are associated with poor neurocognitive outcomes (Luchsinger et al, 2007;Mallorquí-Bagué et al, 2018;Miller & Spencer, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, while research in developed countries has suggested a link between occupation-related PA trends and chronic health issues like obesity, the impact of levels of PA on health in developing countries is not clear. For instance, a recent study conducted in the United States (Zhang et al 2021) found that higher levels of work-related vigorous PA for men and recreational-related moderate PA for women were associated with a reduced risk of abdominal obesity. Similarly, a study conducted in the United Kingdom by Stamatakis and colleagues found that standing/walking occupations were linked to a lower risk of all-cause and cancer mortality as compared to sitting occupations, but no such association was observed in men (Stamatakis et al 2013).…”
Section: Association Between Levels Of Physical Activity and Chronic ...mentioning
confidence: 99%